Taxonomic revision of the genus Glaucocharis Meyrick (Lepidoptera, Crambidae, Crambinae) from China, with descriptions of nine new species - Li, Weichun; Li, Houhun (Zootaxa, 2012)
Glaucocharis Meyrick is revised from China, with descriptions of nine new species: G. brevis sp. n., G. flavifasciaria sp.n., G. paulispinata sp. n., G. grandispinata sp. n., G. siciformis sp. n., G. tridentata sp. n., G. biconvexa sp. n., G.scrotiformis sp. n. and G. setosa sp. n.; Glaucocharis incisella (Bleszynski, 1970) and G. pilcheri Gaskin, 1988 are newlyrecorded for China; the females of seven species are described for the first time: G. omeishani (Bleszynski, 1965), G.incisella (Bleszynski, 1970), G. parmulella Wang & Sung, 1988, G. pilcheri Gaskin, 1988, G. longqiensis Song, 1993, G.huanggangensis Song & Chen, 2001 and G. hastatella Song & Chen, 2001. Images of the adults and illustrations of thegenitalia for the new species are provided. The distribution data of the Chinese Glaucocharis are presented, along with a map showing the localities of these species.